Influence of Parent–Child Interaction on Socio-emotional Development of Children With Perinatal Risks - Lavrova, M; Tokarskaya, L; Kiselev, S (KnE Life Sciences, 2018)
The article is devoted to the study of the influence of peculiarities of child–parent interaction on the early socio-emotional development of children with perinatal risks. This is a relevant area since, first of all, there is an increasing number of children with such risks (especially, with the risk of autism spectrum disorders (ASD) and attention deficit hyperactivity disorder (ADHD)). Moreover, it is parents who can be most instrumental in the successful development, adaptation and socialization of children. The article examines Russian and foreign approaches to the definition of socio-emotional development, stages, and levels of its development. It also analyses the data obtained in the course of research of peculiarities of parent–child interaction with the help of video observation (PCI) that was conducted using the coding scales (SocialinteractionratingScale). In order to assess cognitive, speech, socio-emotional development, and adaptive behavior, «Bayley Scales of Infant Development Third Edition» were used. The data of eight children of the control group (average age 5–8 months) and eight children of the experimental group with family risk of atypical development (older sibling or parent have a confirmed diagnosis of ASD and/or ADHD) (average age 2–66 months) were analyzed. Two-way analysis of variance showed that nondirective behavior of parents can lead to a more successful development of socio-emotional skills of children with the family risk of ASD and ADHD, namely, the skill ‘social setting’. The study is a pilot but demonstrates a potential for further research in this area. Keywords: child–parent interaction, video observation, young children, family risk, socio-emotional development